The Effect of Social Story Telling on Motor Skills and Verbal Communication among the Children and Adolescents (5-17 Years Old) with Severe Autism Spectrum Disorder - Farzaneh Manzari-Tavakoli; Seyed Ebrahim Hosseini; Leyla Karimi (Islamic Azad University, 2018)
Introduction: Autism is one of the structural disorders of brain which is accompanied by deficiency in motor skills and verbal communications. The present study was conducted aiming at investigating the effect of social story telling on the development of motor skills and verbal communications among the children and adolescents suffering the autism. Methods: This study was semi-experimental of pretest- posttest type with control group. Statistical population of this study included all children with autism from 5 to 17 years old in Sirjan City in March 2017- March 2018 from among whom, 16 persons were selected by accessible random sampling method based on the conditions for entering the study, then they were divided randomly into two experimental and control groups. Experimental group was involved with the social stories intervention for children and adolescents through researcher direct training for 12 weeks and 2 sessions a week and control group received no intervention. Research tools were GARS autism rating scale, Vineland social maturity scale and social stories. Results obtained from pretest and posttest stages were analyzed by statistical test of covariance and the significance level was considered at p< 0.05. Results: Finding showed that the social skills training increases significantly the motor skills and verbal communications among the children and adolescents with severe autism spectrum disorder at level of p < 0.001 compared to the control group. Conclusion: Social skills training to autistic children is likely to improve the motor skills and verbal communications among them through strengthening the sensorimotor integration, creativity and motivation for progress and reducing the anxiety.